Pengaruh Subsitusi Tepung Pisang Cavendish terhadap Karakteristik Fisik Kimia dan Organoleptik Crackers : Effect of Cavendish Banana Flour Substitution on the Physical, Chemical and Organoleptic Characteristics of Crackers - Sintawati, Riny; Kurniawati, Elly (Politeknik Negeri Jember, 2024)
Crackers are salty and savory cookies with a crunchy texture. The main ingredient is wheat flour, but innovation by adding cavendish banana flour can reduce the use of wheat flour and increase nutritional value. Banana cavendish has a high economic value and is easily damaged so that it can be processed into flour for preservation and used in food products, one of which is as a substitute for crackers. The purpose of this study was to determine the chemical and organoleptic characteristics and determine the best treatment for cavendish banana flour crackers. This study used the RAL (Completely Randomized Design) method consisting of 5 treatments with 4 replications. The treatment in this study consisted of 5 concentrations of cavendish banana flour 0% (P1), 10% (P2), 20% (P3), 30% (P4), 40% (P5). Data processing using IBM SPSS Statistic 25, the data obtained were analyzed using the ANOVA (Analysis of Variance) method and continued with Duncan's Multiple Range Test (DMRT). The best treatment results on cavendish banana flour crackers are treatment P5 (40% cavendish banana flour) which produces a moisture content 3.40%, protein content 5.59%, crude fiber content 5.42%, and hedonic quality test color slightly yellow-brown, salty taste slightly banana flavor, aroma slightly banana flavor and slightly crunchy texture.